Iron overload in anaemia with underlying haemoglobin constant spring in an antenatal mother in primary care - Thew, Hui Zhu; Ng, Chee Han; Loo, Cheng Yee (BMJ, 2024)
This is the case of a gravida 3 para 1 woman in her late 20s with underlying haemoglobin constant spring who visited a healthcare clinic for an antenatal check-up. Towards the end of her second trimester, she experienced lethargy. During her antenatal booking, she was diagnosed with mild asymptomatic anaemia, high serum ferritin, T saturation of 88 and abnormal liver function tests. She was referred to a hospital where an MRI scan revealed over 2 g of iron deposits in her liver, leading to a revised diagnosis of iron overload. Treatment included deferoxamine and expectant management throughout her antenatal period, and her delivery was uncomplicated. While iron deficiency anaemia is common in pregnancy, it is crucial not to overlook iron deposition and the distinction from acute fatty liver during pregnancy to prevent treatment delays.